Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.3390/50300571
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents of Conyza Albida

Abstract: Alkynes and spathulenol were isolated from Conyza albida (Asteraceae); some of the compounds were lethal against Artemia sp. and cytotoxic against KB cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…(Celastraceae) (Brenniesen and Geisshusler, 1985;Carlini, 2003), Conyza albida Spreng. (Asteraceae) (Pacciaroni et al, 2000;Stamatis et al, 2003), Lippia javanica (Burm. f.) Spreng.…”
Section: Resultsunclassified
“…(Celastraceae) (Brenniesen and Geisshusler, 1985;Carlini, 2003), Conyza albida Spreng. (Asteraceae) (Pacciaroni et al, 2000;Stamatis et al, 2003), Lippia javanica (Burm. f.) Spreng.…”
Section: Resultsunclassified
“…Terpinen-4-ol can induce caspase-dependent apoptosis in human melanoma cells [7], and has been shown to cause differentiation of human myelocytic cell line HL-60 [8]. Furthermore, spathulenol has a GI 50 value of 83.8 μM when tested in the KB cell cytotoxicity assay and can moderately inhibit human topoisomerase I [9]. Limonene, terpinen-4-ol and spathulenol are all found in high concentrations in the essential oil, which could explain, in part, the anticancer activity.…”
mentioning
confidence: 99%
“…Other studies reported that an AEE of Conyza bonariensis also showed cytotoxicity with the brine shrimp ( Artemia ssp.) toxicity test [ 13 ]. Moreover, four compounds isolated from C. albida exhibited cytotoxic activities against the tumor KB cell line at concentrations of 7–19 μ g/mL [ 13 ].…”
Section: Discussionmentioning
confidence: 99%